Analyze Modified Extended Information Technology Continuance toward Continuance Intention of Administration Information System - Lusia Tria Hatmanti Hutami (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study emphasizes the importance of the role of technology in the form of information systems in an educational service institution by using an information system application that is used by the academic community on a daily basis. The purpose of this study is to analyze post-usage usefulness and facilitating conditions through or not through satisfaction to achieve continuance intention related to Administrative Information Systems (SIA) at the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa, Yogyakarta. This study uses a modification of the Extended Information Technology Continuance (ITC). This study uses AMOS 22 path analysis and a total sample of 343 students in accounting and management programs. The results showed that all hypotheses were accepted except for the direct effect of facilitating conditions toward continuance intention. These results strengthen the impact of satisfaction on continuance intention regarding the practice of using technology. The implication of the results indicates that the use of available information system applications, although satisfactory, must still be monitored and developed in order to ensure continued user satisfaction.